The Use of DFSS Tool / Design for Six Sigma in the Innovative Process of New Product Development: a Case Study - Martins, Sara (2019)
The SS methodology is being widely used as a quality management model. Focusing on "Zero Defects" production, the tool that support DNP used in the planning phases, that precede manufacturing is DFSS methodology, suitable for production processes with SS requirement. There is a contradictory question regarding the differences and complementarities between DFSS tool and the SS methodology: to conclude about what is the best strategic decision by two companies, in which one uses the SS and the other uses the DFSS; else more, if it would be a competitor at a higher level with regard to the experience and knowledge, by using both. The case study indicates that given the intrinsic characteristics of the company, common to other Portuguese Small, Medium Enterprises (SMEs), it is clear that the use of DFSS tool turns out to be the most effective, especially when the client is a big company.